Addressing Maternal Mental Health among Black Perinatal Women in Atlanta, Georgia: a CBPR approach - Natalie Hernandez (Georgia Southern University, 2022)
Background: Perinatal mood and anxiety disorders (PMADs) are the most common complication of pregnancy, affecting up to 1 in 5 childbearing women, with higher rates among low-income minority women. One in seven women suffer from perinatal depression. This study aimed to (1) assess the mental and emotional health challenges of underserved Black perinatal women in Atlanta, Georgia (GA) and (2) examine local priorities and sources of care for mental health among underserved women in Atlanta, GA. Methods: A community-based participatory research partnership between Morehouse School of Medicine (MSM) and the Center for Black Women's Wellness (CBWW)'s Atlanta Healthy Start Community Action Network (AHSI-CAN) conducted a mixed-methods study to examine the mental/emotional health challenges of underserved Black women in Atlanta, GA. Questionnaires were completed with Black perinatal women (n=345). Semi-structured interviews were conducted with Black perinatal women (n=5), health care professionals (n=9) and outreach workers (n=3) to gather perspectives regarding local priorities for maternal mental health care in their communities. Interviews are still being conducted due to delays and impact of COVID-19. Results: More women reported at least one mental health challenge after pregnancy when compared to prior to pregnancy (i.e., 71% vs 32%). Many women reported (73%) being asked about their emotional and mental health, however, only 16% were queried by an obstetrician. Further preliminary descriptive statistics on other PMADs risk factors are reported. This paper describes the procedures that were implemented to complete this study. Conclusions: This study addresses critical gaps in current knowledge about PMADS among Black women. Preliminary analyses indicate that PMADS are alarmingly high among this sample of Black perinatal women in Atlanta, GA. The knowledge gained from this formative research will provide researchers and community-based organizations (CBOs) with relevant data that will inform approaches and models to address Black maternal mental health.